Three new species of the genus Hexarhopalus Fairmaire, 1891 (Coleoptera, Tenebrionidae: Cnodalonini) from China - Jiang, Ri-Xin; Li, Ze-Chuan; Ji, Quan-Yu; Engel, Michael S.; Wang, Shuo (Zootaxa, 2021)
Three new species of the genus Hexarhopalus Fairmaire, 1891 are described and figured from China: Hexarhopalus (Hexarhopalus) yunnanensis sp. nov. from Yunnan, Hexarhopalus (Hexarhopalus) zhuxiangi sp. nov. from Guangxi, and Hexarhopalus (Leprocaulus) nanlingensis sp. nov. from Guangdong. A revised key is provided to the species of Hexarhopalus from China.